ENHANCING ANTIOXIDANT STATUS, PRODUCTIVE AND REPRODUCTIVE PERFORMANCE FOR POST-MOLT BROILER BREEDERS BY USING MACA POWDER (LEPIDIUM MEYENII) - Mohammad A. Elsagheer*1 and M. Kh. Wadea2, Nada M. Ali3, Mohamed R. Eletmany*4,5, (Chelonian Research Foundation, 2024)
This study was designed to evaluate the effects of using Maca powder (Lepidium meyenii) in the diet on egg production traits, fertility, hatching characteristics, and some blood parameters for broiler breeders (Arbor-Acres Plus) post-molting. A total of 180 Females and 15 Males, 62 weeks old, Arbor Acres Plus broiler breeders were induced to forced molting with ZnO in diet with a moderate decrease in lighting schedule from 16 to 8 h and feed restriction at 50 g/bird daily. Post-molting birds were randomly divided into three groups according to Maca powder as follows: the 1st group (M0) was fed the basal diet without Maca, while the 2nd (M1) and the 3rd (M2) groups were fed the basal diets supplemented with Maca powder at the levels of 1 and 2g Maca/kg diet, respectively.All groups were replicated into five replicates of 13 birds each (1 male + 12 females). The trial lasted for 12 weeks. According to the present study, the laying rate was significantly (P<0.05) increased by using Maca powder at different levels, without affecting egg weight and egg mass. Furthermore, the fertility rate and hatchability of settable eggs were significantly (P<0.05) increased by using Maca powder at 1 and 2g /kg diet. Additional results showed that using Maca powder significantly (P<0.05) decreased early embryonic mortality rate compared with control. Data indicated that Maca had no significance on the hatchability of fertile eggs, chick weight, and late embryonic mortality rate. The results of blood biochemical parameters revealed that serum cholesterol was significantly (P<0.05) reduced by using Maca powder. Data indicated that TSD and TAOC were significantly (P<0.05) higher in the M1 and M2 groups compared with control. It could be concluded that Maca powder (Lepidium meyenii) administration in diets for post-molt broiler breeders at levels of 1 and 2g /kg could be improved productive and reproductive traits also, enhance antioxidant status. Keywords: Maca powder, broiler breeders, performance, antioxidant status, molting